Influence Brand Awareness, Product Variations and Word of Mouth Towards Customer Satisfaction at Coffee Shop Tuku Cipete Branch, South Jakarta - Junila Putri Mustika Sari; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the influence of the independent variables of this study in the form of brand awareness variables, product variation variables and word of mouth variables on the dependent variables of this study with customer satisfaction variables at Coffee Shop Cipete South Jakarta Branch. The method in this study is descriptive-quantitative with a population in the form of respondents or, more specifically, consumers of Coffee Shop Tuku. The sample of research respondents was 100 using non-probability sampling techniques. In using non-probability sampling techniques, the pieces are expected to meet the conditions or criteria required in this study. The data used was in the foata through the distribution of questionnaires with model tests in the form of multiple linear regression processed using SPSS 25. The results were obtained after data processing analysis with the following conclusions: Brand Awareness, Product Variations, and Word of Mouth positively and significantly affect Customer Satisfaction. It was previously tested against statements that were declared valid and reliable.